A physically based universal functional to characterize the mechanism of fatigue crack growth in materials. (October 2015) - Ravi Chandran, K.S.
Abstract: A unique relationship between the normalized remaining section size and the normalized remaining fatigue life has been discovered to exist during fatigue crack growth in a wide spectrum of materials. A crack growth functional that relates the two variables, and which is in excellent agreement with experimental data, is proposed. This functional suggests that all fatigue cracks propagate uniquely to sever the material cross-section and is promising as a new physical basis for characterizing fatigue crack growth mechanisms in materials.